Compartmentalization of cAMP Signaling in Adipogenesis, Lipogenesis, and Lipolysis - Rogne, M.; Taskén, K. (Hormone and Metabolic Research, 2014)
Energy storage and release at times of food excess or fasting are carefully coordinated processes that depend on the appropriate differentiation of mesenchymal stem cells into mature adipocytes (adipogenesis) forming white adipose tissue (WAT) and on regulatory signals for storage (lipogenesis) or mobilization (lipolysis) of triacylglycerides (TAGs) from lipid droplets. It is widely recognized that cAMP signaling via protein kinase A (PKA) is important both in adipogenesis and for hormonal control and lipolysis in WAT. A kinase anchoring proteins (AKAPs) target PKA to distinct subcellular compartments in close proximity to its specific substrates thereby providing spatial and temporal specificity in the mediation of biological effects controlled by the cAMP-PKA pathway. This review will provide an updated overview of some of the sites of regulation by cAMP in adipogenesis and lipolysis and the involvement of AKAPs and highlighting, as a recent example, the AKAP Optical Atrophy 1 (OPA1) and its role in the phosphorylation of Perilipin to induce lipolysis.
Keywords: fat cell; adipose tissue; stem cells